2006
DOI: 10.1177/0013161x06289675
|View full text |Cite
|
Sign up to set email alerts
|

The Unintended Consequences of a Standardized Knowledge Base in Advancing Educational Leadership Preparation

Abstract: Background: The quest for a “knowledge base” in educational administration resulting in the construction of national standards for preparing school leaders has brought with it an unexpected downside. Purpose: It is argued that instead of raising the bar for preparing educational leaders, the standards have lowered them, first by embracing only a limited set of the actual responsibilities of school leaders, resulting in programmatic reductionism, and permitting the licensing of school leaders at sites outside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 15 publications
1
72
0
8
Order By: Relevance
“…Nor as Donmoyer and others have argued do we believe a singular, uncontested, normalized knowledge base is warranted or possible (e.g., Anderson et al, 2002;Donmeyer, 1999;English, 2006;Littrell & Foster, 1995;Scheurich, 1995). Rather, as Scheurich (1995) has argued, our goal is to trigger alternative forms of discourse and action focused on improving the lives and outcomes of nondominant students.…”
Section: Standard 2 Ethics and Professional Normsmentioning
confidence: 91%
“…Nor as Donmoyer and others have argued do we believe a singular, uncontested, normalized knowledge base is warranted or possible (e.g., Anderson et al, 2002;Donmeyer, 1999;English, 2006;Littrell & Foster, 1995;Scheurich, 1995). Rather, as Scheurich (1995) has argued, our goal is to trigger alternative forms of discourse and action focused on improving the lives and outcomes of nondominant students.…”
Section: Standard 2 Ethics and Professional Normsmentioning
confidence: 91%
“…Using my own variation of an argument advanced by English (2003English ( , 2006English ( , 2008, I argue against the notion of leadership standards in general, but do not review individually the Interstate School Leaders Licensure Consortium (ISLLC) Standards or the Principal Quality Practice Guideline (PQPG) that may soon become a requirement in Alberta. Common concerns related to leadership standards might include the static and arbitrary nature of the relevant body of knowledge, the reductionist approach taken in defining it, and the discounting of judgment and experience in assessment for accreditation.…”
Section: Leadership Standards: a Regime Of Truthmentioning
confidence: 99%
“…English (2006) asserts the ISLLC standard has "not only proven detrimental to the profession generally, and the professoriate specifically, but that it has actually lowered the standards for leadership preparation" (p. 462). Why?…”
Section: Leadership Standards: a Regime Of Truthmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, national research reports have focused on a need to improve school leadership preparation programs (Darling-Hammond, LaPointe, Meyerson, & Orr, 2007;Levine, 2005), while scholars in the field of education leadership have emphasized that preparation program improvement is essential to overall school improvement (Murphy, 1999(Murphy, , 2002Scribner & Bredeson, 1997). Furthermore, education leadership researchers have suggested that conventional principal preparation programs were not aligned with the knowledge, skills, and behaviors required by principals to function effectively on a day-to-day basis (English, 2006;Fossey & Shoho, 2006;Hess & Kelly, 2007). In general, preparation programs for school administrators have been criticized for being deficient in several areas, including recruitment of quality candidates, collaboration between university faculty and practitioners, and relevant curriculum (Jackson & Kelley, 2002).…”
mentioning
confidence: 99%